A Comparison of Clinical Outcomes in Patients of Mandibular Condyles Fractures Treated with Open Versus Close Reduction - Nasir Abbas, Asif Nazir, Fahad Khaliq, Tanveer Ahmed Khan, Ali Iftikhar, Sidra Tul Muntaha, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The absence of a widely acknowledged and conclusive therapy for condylar fractures is a matter of contemporary debate and contention, with the issue of whether surgical or conservative approaches are better suitable for managing such fractures being unresolved. This study investigates several methodologies pertaining to the conservative, closed, and open surgical interventions for the treatment of condylar fractures. The standardization of fracture classification systems and treatment techniques is necessary to provide a clear and optimum strategy for individual individuals and their respective fractures. Objectives: The objectives of the study are to compare clinical outcomes in patients of mandibular condyles fractures treated with open versus close reduction. Method: A total of 84 individuals diagnosed with subcondylar fractures of the mandible were assessed. All fractures seen in the study exhibited displacement, with either angulation ranging from 10° to 35° or a reduction in length of the ascending ramus by more than 2 mm. A comprehensive assessment, including both clinical and radiographic examination, was conducted at the 6-month mark after the occurrence of the trauma. The clinical criteria assessed in this study included mouth opening, temporomandibular joint (TMJ) discomfort, mandibular deviation, malocclusion, facial damage, and scar formation. Results: The findings indicated a statistically significant difference between the two groups, with a p-value of less than 0.05. The findings suggest that open reduction was found to be more efficacious than closed reduction in enhancing mouth opening, mandibular deviation, TMJ discomfort, and malocclusion. Conversely, closed reduction was shown to be more beneficial than open reduction. Conclusion: The study findings indicate that the open treatment approach yields superior progress compared to closed techniques, and these differences are statistically significant. Patients who had open reduction demonstrated considerably superior results in all functional measures, with the exception of facial nerve damage and scar formation, when compared to those who underwent closed reduction. Keyword: Mandibular fracture, open reduction, closed reduction, clinical outcome